Alkyl Length Effects on the DNA Transport Properties of Cu (II) and Zn(II) Metallovesicles: An In Vitro and In Vivo Study. (11th November 2018) - Arroyo, Itizia Z.; Gomez, Clarissa; Alarcon, Hugo; Jimenez, Araceli; Pardo, Andrew; Montaño, Gabriel; Armijos, Rodrigo X.; Noveron, Juan C.
Abstract : Cationic liposomes with DNA-transportation properties have attracted considerable attention for their ability to deliver medicinal oligonucleotides to mammalian cells. Amongst these are metalloliposomes that use transition metal ions to confer the lipid molecules cationic charge and unique advantages such as redox- and ligand-exchange triggered DNA-release properties. In this study, lipophilic copper (II) and zinc (II) complexes of 1-alkyl-1, 4, 7-triazacyclononane were prepared to investigate their ability to bind and transfect double stranded DNA with mammalian cells in vitro and in vivo. The copper(II)-surfactant complexes Cu(TACN-C8)2 (1 ), Cu(TACN-C10)2 (2 ), Cu(TACN-C12)2 (3 ), Cu(TACN-C14)2 (4 ), Cu(TACN-C16)2 (5 ), and Cu(TACN-C18)2 (6 ) that comprise ligands that vary in the length of the alkyl group and the zinc (II)-surfactant complex of Zn(TACN-C12 )2 (7 ) were synthesized. The critical micelle concentration (CMC) for 1-7 was measured using fluorescence spectroscopy and an evaluation of the transfection efficiency of the complexes was assessed using the pEGFP-N1 plasmid and HEK 293-T cells. An inverse relationship between DNA transfection efficiency and CMC of the Cu(II) metallosurfactants was observed. The highest transfection efficiency of 38% was observed for Cu(TACN-C12)2 corresponding to the surfactant with dodecyl alkyl chain having a CMC of 50 μ M. Further, an in vivo experiment using mice models was conducted to test the Cu(TACN-C12)2 (3 ) and Zn(TACN-C12)2 (7 ) metallosurfactants delivering a DNA vaccine designed for protection against leishmaniasis disease and the study revealed that the Cu-lipoplex elicited the production of significantly more T cells than the Zn-lipoplex and the control group in vivo.